2006
DOI: 10.1089/jmf.2006.9.562
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycemic Effect of Umbelliferone in Streptozotocin-Diabetic Rats

Abstract: The present study was designed to investigate the antihyperglycemic effect of Umbelliferone (UMB) in normal and streptozotocin (STZ)-diabetic rats. Diabetes was induced in adult male albino rats of the Wistar strain, weighing 180-200 g, by administration of STZ (40 mg/kg of body weight) intraperitoneally. Diabetic rats showed an increase in levels of blood glucose and glycosylated hemoglobin (HbA(1c)) and activities of gluconeogenic enzymes such as glucose-6-phosphatase and fructose-1,6-bisphosphatase, and a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
95
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(105 citation statements)
references
References 22 publications
7
95
0
3
Order By: Relevance
“…This point is in agreement with the findings of other reports (Greene and Lattimer, 1983;Kim et al, 2006;Mazloomi et al, 2010;Musabayane et al, 1995;Ramesh and Pugalendi, 2006;Sajedianfard et al, 2013). In the diabetic control group, from the first day until the end of the study weight loss was 24.5%.…”
Section: Discussionsupporting
confidence: 93%
“…This point is in agreement with the findings of other reports (Greene and Lattimer, 1983;Kim et al, 2006;Mazloomi et al, 2010;Musabayane et al, 1995;Ramesh and Pugalendi, 2006;Sajedianfard et al, 2013). In the diabetic control group, from the first day until the end of the study weight loss was 24.5%.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, esculetin and quercetin showed almost the same moderate inhibitory activity toward sucrase, with IC 50 values of 72 and 71 µM, respectively ( Table 1), but the suppressive effects on the blood glucose levels were obviously greater in the esculetin-treated group. Ramesh et al (27) have reported that umbelliferone significantly elevated the plasma insulin level as compared with nontreated diabetic rat, and it caused a reduction in the blood glucose level. In the present study, we were not able to find any significant inhibitory activity of umbelliferone (1) against R-amylase, maltase, and sucrase ( Table 1).…”
Section: Results and Disussionmentioning
confidence: 99%
“…A wide range of pharmacological activities of HOC is demonstrated in animal studies. The compound lowers serum GLU (glucose) level in rats with streptozotocin diabetes, exhibit antioxidant, antinociceptive and anti-inflammatory effects, is used as derivative in the synthesis of drugs [2][3][4][5][6][7]. The recent study showed that HOC is α-amylase and α-glucosidase inhibitor in vitro [8], causes neuroprotective effects [9,10], attenuate alcohol-induced fatty liver in rats [11].…”
mentioning
confidence: 99%